Análise dos impactos ambientais decorrentes da ocupação Vista Alegre do Juá, Santarém, PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2018)
One of the main changes in Brazilian cities is the accelerated growth, often irregular and without planning, which ends up causing serious socio-environmental problems. Based on this, this study analyzes the Environmental Impacts resulting from the occupation Vista Alegre of Juá, located in the Municipality of Santarém-PA. The methodology is characterized as descriptive, utilizing for data collection bibliographic research, documentary and field study. In the field study stage, in situ visits were carried out for the application of a questionnaire and the check list method, for the identification of environmental impacts. It was verified that in the occupation reside approximately 3.000 thousand families distributed in an area that lacks basic services like sanitation, health, education and infrastructure. This situation compromises the quality of life of the population and contributes to the enhancement of environmental impacts in the area, such as silting of Juá Lake, floods, erosion, water soil and air pollution. Thus, it is possible to observe that the occupation is associated with the real estate deficit and the absence of Housing Policies in the Municipality, causing the housing vulnerability of families who seek housing the environmental commitment of the area.
Keywords: Crescimento urbano; Degradação ambiental; Habitação; Santarém; CNPQ:: ENGENHARIAS